2017
DOI: 10.1016/j.firesaf.2017.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Auto-extinction of engineered timber: Application to compartment fires with exposed timber surfaces

Abstract: The following journal and conference papers have been published over the course of this thesis. Where these are based on part or whole of a chapter of this thesis, this is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 94 publications
4
37
0
1
Order By: Relevance
“…This is a significant difference between the two tests (approximately 50%), despite the energy provided by the natural gas being very similar between the two tests. This difference can be partially attributed to the variability of a natural material such as timber, as well as the stochastic nature of delamination, which can result in unpredictable and often very different behaviour from apparently identical test specimens …”
Section: Energy Analysessupporting
confidence: 88%
See 3 more Smart Citations
“…This is a significant difference between the two tests (approximately 50%), despite the energy provided by the natural gas being very similar between the two tests. This difference can be partially attributed to the variability of a natural material such as timber, as well as the stochastic nature of delamination, which can result in unpredictable and often very different behaviour from apparently identical test specimens …”
Section: Energy Analysessupporting
confidence: 88%
“…During the compartment fire experiments, it was observed that the CLT slabs continued to combust (through surface oxidation) for several hours after burnout of the compartment fuel load. This is consistent with findings from previous compartment fire experiments . This observation may have important implications for the fire resistance design of both encapsulated and unprotected mass timber elements as when testing combustible materials, they may continue burning without added fuel if no immediate active fire intervention is made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, previous studies have largely focused on studying ignition to identify a single ignition criteria (temperature, mass loss rate, or heat flux). The extinction of wood has been treated in a similar manner to identify either a critical heat flux [11] or a critical mass loss rate [12].…”
Section: Introductionmentioning
confidence: 99%